Risk of suicide, suicide attempt, and suicidal ideation among people with vitamin D deficiency: a systematic review and meta-analysis - Jia Yu; Sumayya Nadhim Mohammad; Lusine G. Khachatryan; Jaafaru Sani Mohammed; Soumya V. Menon; Mandeep Kaur; Ibrokhim Sapaev; Majid S. Jabir; Beneen Husseen; Hosein Azizi (BMC Psychiatry)
Abstract Background Evidence shows that vitamin D affects brain function. Transcription of over 1000 genes is known to be controlled by vitamin D, potentially contributing to the neurotrophic and neuroprotective effects that can influence suicidal behavior. Several investigations with contradicting findings have identified an association between suicidal behaviors (SBs) or depressive symptoms and low vitamin D levels. This meta-analysis aimed to analyze the pooled association between vitamin D deficiency and the risk of suicide, suicide attempt (SA), and suicidal ideation (SI). Methods A systematic search was performed through PubMed, Web of science (ISI), Scopus, Embase, and grey literature up to 10 October 2024. Meta-analysis included observational studies that assessed the association between SBs and vitamin D blood serum level and/or vitamin D deficiency. After screening and quality assessment, meta-analysis and sensitivity analysis using random effects model were carried out to estimate the pooled odds ratios (ORs) for the risk of suicide, SA, and SI. We also calculated pooled standard mean difference (SMD) of vitamin D levels between control subjects and patients with SBs. Results A total of 14,095 records were identified. Finally, 13 studies participating 515,406 subjects were included in the meta-analysis after eligibility assessment. Vitamin D deficiency non-significantly increased the risk of suicide, SA, and SI (OR = 1.7; 95% CI: 0.93 – 3.12), (OR = 1.65; 95% CI: 0.98 – 2.80), and (OR = 1.15; 95% CI: 0.94 – 1.41), respectively. However, levels of vitamin D in patients with SBs were significantly lower than in controls without any SBs (SMD = -0.69; 95% CI: -0.89 – -0.49). Conclusion The results of this meta-analysis indicated that vitamin D levels are lower among patients with SBs. These findings can inform suicide prevention programs, particularly for target groups experiencing significant vitamin D deficiency.